Answer:
1) f
4 * ¼ = 1 (Multiplicative inverse property)
2) c
6 * 1 = 6 (Identity property of multiplication)
3) h
5 + 7 = 7 + 5 (Commutative property of addition)
4) j
If 5 + 1 = 6 and 4 + 2 = 6, then 5 + 1 = 4 + 2 (Transitive property)
5) a
4(x - 3) = 4x - 12 (Distributive property)
6) i
3(5) = 5(3) (Commutative property of multiplication)
7) k
Rules that allow us to take short cuts when solving algebraic problems.(Properties)
8) d
5 * (3 * 2) = (5 * 3) * 2 (Associative property of multiplication)
9) g
4 + (-4) = 0 (Additive inverse property)
10) e
2 + 0 = 2 (Identity property of addition)
11) b
A + (B + C) = (A + B) + C (Associative property of addition)
Answer:
-4
Step-by-step explanation:
<u>Step 1: Combine</u>
Adding a negative number is same as subtracting a number.
-1.6 + (-2.4)
-1.6 - 2.4
-4
Answer: -4
Answer:
x=−2
Step-by-step explanation:
1 Expand.
6-2x-12=3x+4
6−2x−12=3x+4
2 Simplify 6-2x-126−2x−12 to -2x-6−2x−6.
-2x-6=3x+4
−2x−6=3x+4
3 Add 2x2x to both sides.
-6=3x+4+2x
−6=3x+4+2x
4 Simplify 3x+4+2x3x+4+2x to 5x+45x+4.
-6=5x+4
−6=5x+4
5 Subtract 44 from both sides.
-6-4=5x
−6−4=5x
6 Simplify -6-4−6−4 to -10−10.
-10=5x
−10=5x
7 Divide both sides by 55.
-\frac{10}{5}=x
−
5
10
=x
8 Simplify \frac{10}{5}
5
10
to 22.
-2=x
−2=x
9 Switch sides.
x=-2
x=−2
Answer:
C) -7/3
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(9-(-5))/(-2-4)=(9+5)/-6=14/-6
simplify -14/6 to -7/3